การวิเคราะห์ระดับอันตรายจากแผ่นดินไหวในประเทศลาว - สุรพงษ์ เลิศฤทธิพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
According to the present-day activities of the Indian-Eurasian plate collision, Laos and the adjacent areas dominated by a large number of seismic source zones, in particular for the northern part. Based mainly on the epicentral distribution of instrumental earthquake records, it is indicated that most of seismic source zone mentioned above are active. Therefore, Seismic Hazard Analysis (SHA) in Laos is necessary for mitigation planning of the forthcoming earthquake hazards. In this study both deterministic (DSHA) and probabilistic (PSHA) scenarios of SHA are analyzed covering the whole country of Laos, i.e., Latitude of 14๐ N - 23๐ N and Longitude of 100๐ E - 108๐ E. The results obtained from this SHA are present in terms of maps showing distribution of the peak ground acceleration (PGA). DSHA results reveal that the seismicprone areas of Laos are located in the northern part with the PGA ranges 0.55 – 0.65g. Meanwhile for 2% probability of exceedance for a 50 year period of the PSHA, the PGA of the northern part are around 0.3 – 0.45 g covering a number of major cities of Laos, i.e., Phongsali, Louang Namtha, Louangphrabang, Xaignbouli, and Vientiane. For 10% probability of exceedance for a 50 year period, the PGA are estimated about 0.2 – 0.35 g. Whilst, PGA maps for 2% probability of exceedance for a 50 year period also has the similar hazard distribution of the 10% exceedance for a 50 year. However, the ground shaking has increased over 1.5 levels approximately.